Coastal environmental changes after the Saemangeum seawall construction - Baek, Ji-Yeon; Guerreiro, Catarina V.; Kim, Jaeseong; Nam, Jungho; Jo, Young-Heon (Frontiers in Marine Science, 2024)
The coastal environment in the Saemangeum area has experienced persistent physical stresses owing to the irregular operation of the sluice gates and related artificial disturbances since seawall construction, which has led to restricted freshwater-seawater circulation. To understand the impacts of stress, we performed long-term (1999-2022, 24 years) in situ measurements of relevant biotic and abiotic parameters and employed the random forest (RF) technique to determine the phytoplankton community response to environmental disturbance. Specifically, we estimated chlorophyll-a (Chl-a) concentrations using an RF model based on various environmental factors such as sea surface temperature (SST), sea surface salinity (SSS), dissolved oxygen saturation (DO), dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (DIP) as input variables. From the RF analysis, each environmental factor contributed to variation in Chl-a concentration as follows: SSS (42.91%), SST (17.88%), DIP (14.38%), DIN (13.36%), and DO (11.48%). In addition, we performed sensitivity experiments by altering the salinity, which was revealed to be the most influential environmental parameter. As a result, Chl-a concentration increased by approximately 1.79 times in lower salinity conditions (from 7 to 27 psu) compared to the normal salinity conditions prior to the seawall construction (from 12 to 32 psu) in both areas, including the inside and outside the seawall. More importantly, lower salinity conditions stimulated dinoflagellate blooms, that is, red tides, implying that restricted freshwater-seawater circulation could worsen coastal ecosystems. Thus, this study contributes to understanding the impacts of environmental changes caused by sluice gate manipulation on marine ecosystems, such as phytoplankton community dynamics. Moreover, this study recommends an ecologically suitable operation scheme for Saemangeum sluice gates to ensure a healthy coastal ecosystem.